Upper Extremity DVT versus Lower Extremity DVT: Perspectives from the GARFIELD-VTE Registry - Ageno, Walter; Haas, Sylvia; Weitz, Jeffrey I.; Goldhaber, Samuel Z.; Turpie, Alexander G. G.; Goto, Shinya; Angchaisuksiri, Pantep; Dalsgaard Nielsen, Joern; Kayani, Gloria; Farjat, Alfredo E.; Zaghdoun, Audrey; Schellong, Sebastian; Bounameaux, Henri; Mantovani, Lorenzo G.; Prandoni, Paolo; Darius, Harald; Kakkar, Ajay K. (Thrombosis and Haemostasis, 2019)
Upper extremity deep vein thrombosis (UEDVT) is less common than lower extremity DVT (LEDVT) and consequently less well characterized. This study compared clinical characteristics and 1-year outcomes between 438 UEDVT patients and 7,602 LEDVT patients recruited in the GARFIELD-VTE registry. UEDVT patients were significantly more likely to have a central venous catheter than those with LEDVT (11.5% vs. 0.5%; p < 0.0001), and had a higher rate of active cancer (16.2%) or recent hospitalization (19.4%) compared with LEDVT patients (8.7% and 11.2%, respectively). Nearly all patients with UEDVT and LEDVT were initiated on anticoagulant therapy, which was a direct oral anticoagulant in one-third individuals in both groups. At 3, 6, and 12 months, the proportion of UEDVT and LEDVT patients who were receiving anticoagulant therapy was 82.6 and 87.4%, 66.0 and 72.6%, and 45.7 and 54.6%, respectively. In the UEDVT and LEDVT groups, VTE recurrence rate was 4.0 (95% confidence interval [CI], 2.4–6.7) and 5.5 (95% CI, 4.9–6.1) per 100 person-years, respectively; major bleed was noted in 1.3 (95% CI, 0.6–3.2) and 1.6 (95% CI, 1.3–1.9) per 100 person-years and all-cause mortality in 9.7 (95% CI, 7.1–13.4) and 6.7 (95% CI, 6.1–7.3) per 100 person-years, respectively. Hence, risk of recurrence was similar in the two groups whereas all-cause mortality was significantly higher in the UEDVT group than the LEDVT group (p = 0.0338). This latter finding was likely due to the high prevalence of cancer in the UEDVT group.
Keywords: upper extremity deep vein thrombosis; lower extremity deep vein thrombosis; direct oral anticoagulant; venous thromboembolism; GARFIELD-VTE registry